2018
DOI: 10.1002/cam4.1824
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐driven like macrophages induced by conditioned media from pancreatic ductal adenocarcinoma promote tumor metastasis via secreting IL‐8

Abstract: Tumor‐associated macrophages (TAMs) are abundant population of inflammatory cells which play an essential role in remodeling tumor microenvironment and tumor progression. Previously, we found the high density of TAMs was correlated with lymph node metastasis and poor prognosis in pancreatic ductal adenocarcinoma (PDAC). Therefore, this study was designed to investigate the mechanisms of interaction between TAMs and PDAC. THP‐1 monocytes were the exposure to conditioned media (CM) produced by PDAC cells; then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…2e), but the mechanism of TAMs inducing the EMT of pancreatic cancer cells was not elucidated in this study. Recent reports by others suggested that IL-8 [30], CCL20 [31], and the TLR4/IL10 signaling pathway [15] might be associated with EMT-induction in an in vitro culture system, and further investigations will be necessary to uncover the precise mechanism of EMT induction through the interplay between pancreatic cancer and TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…2e), but the mechanism of TAMs inducing the EMT of pancreatic cancer cells was not elucidated in this study. Recent reports by others suggested that IL-8 [30], CCL20 [31], and the TLR4/IL10 signaling pathway [15] might be associated with EMT-induction in an in vitro culture system, and further investigations will be necessary to uncover the precise mechanism of EMT induction through the interplay between pancreatic cancer and TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CXCL8 in urine specimens and the tumour microenvironment of bladder cancer patients is significantly higher than that of healthy volunteers (Pignot et al, 2009;Sheryka et al, 2003), and the overexpression of CXCL8 is positively correlated with significantly reduced survival of patients overall (Zhang et al, 2014). It has been shown that TAMs in the solid tumour microenvironment can secrete CXCL8 in large amounts, directly contributing to the progression of pancreatic ductal carcinoma, papillary thyroid cancer, colorectal cell carcinoma, and esophageal squamous cell carcinoma (Chen et al, 2018;Fang et al, 2014;Hosono et al, 2017;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that tumor-associated macrophages (TAMs) were abundant in the tumor microenvironment (TME) of PDAC (Chen et al 2018 ; Habtezion et al 2016 ; Zhu et al 2017 ). Therefore, TAMs may be a useful therapeutic target against PDAC.…”
Section: Introductionmentioning
confidence: 99%